A material point method based ploughing model to study the effect of asperity geometry on the ploughing behaviour of an elliptical asperity. (February 2020) - Mishra, Tanmaya; de Rooij, Matthijn; Shisode, Meghshyam; Hazrati, Javad; Schipper, Dirk J.
Abstract: A material point method (MPM)-based numerical model has been used to study the effect of asperity size and orientation relative to sliding direction on the ploughing behaviour of a rigid, ellipsoidal asperity. Based on the simulated ploughing behaviour, an analytical model has been extended to calculate the ploughing depths over the wear track and compute the forces acting over the contacting surface of an ellipsoidal asperity sliding through a rigid-plastic substrate. The analytical model results have been compared with the MPM model results. The MPM model results are also validated to be in good agreement with the friction forces and ploughing depths measured from the ploughing experiments on lubricated steel sheets with ellipsoidal indenters up to certain sizes and orientations. Highlights: Ploughing depth of substrate computed by analytical model for ellipsoidal asperity. Components of friction force acting on the asperity computed from contact profile. Ploughing experiments and simulations done for ellipsoidal pins on lubricated steel. Friction and ploughing depths obtained from MPM model are experimentally validated. Effect of size and orientation of asperity and applied load on ploughing is studied.